2000
DOI: 10.1093/gerona/55.8.m463
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Elderly Persons: Its Prevalence and Associated Cardiovascular Risk Factors in Tainan City, Southern Taiwan

Abstract: Background. Hypertension was the eighth leading cause of death in Taiwan in 1996, and the prevalence of hypertension has increased recently. The purpose of the study was to assess the prevalence of hypertension and its associated cardiovascular risk factors in elderly persons in Tainan City, southern Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 39 publications
9
35
3
1
Order By: Relevance
“…Another Singaporean study using the same definition of hypertension as we did, although not limited to the elderly, did report a prevalence of hypertension among those aged X65 years that was comparable with our findings. 6 Similar to previous studies, 14,[16][17][18]20,22,23,25,26 we observed hypertension to be associated with age, higher BMI and diabetes. We also observed elderly men to be at a higher risk of hypertension, whereas previous studies have reported either no association with gender, 17,20 or a higher risk for women.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Another Singaporean study using the same definition of hypertension as we did, although not limited to the elderly, did report a prevalence of hypertension among those aged X65 years that was comparable with our findings. 6 Similar to previous studies, 14,[16][17][18]20,22,23,25,26 we observed hypertension to be associated with age, higher BMI and diabetes. We also observed elderly men to be at a higher risk of hypertension, whereas previous studies have reported either no association with gender, 17,20 or a higher risk for women.…”
Section: Discussionsupporting
confidence: 89%
“…36 The prevalence of hypertension and its awareness, treatment and control in studies conducted exclusively among the elderly and using our criteria for defining hypertension is given in Table 5. 14,15,17,[19][20][21][22][23][24][25][26][27] Although most of these studies reported a lower prevalence of hypertension 17,20,[22][23][24][25]27 than what we observed (73.9%), some Hypertension among elderly Singaporeans R Malhotra et al reported a similar prevalence 14,19,21,23,26 or, in one study, 15 an even higher prevalence. Other than differences in the BP measurement instrument (manual or electronic) and number of readings (two or three) used for defining SBP and DBP, the variation could also reflect differences in demographic (for example, age, gender, ethnicity) and lifestyle (for example, diet, physical activity) profiles and in economic development across countries (prevalence is usually higher in more developed economies 38 ).…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations